2020
DOI: 10.1111/cyt.12828
|View full text |Cite
|
Sign up to set email alerts
|

Impact of image analysis and artificial intelligence in thyroid pathology, with particular reference to cytological aspects

Abstract: Objective Thyroid pathology has great potential for automated/artificial intelligence algorithm application as the incidence of thyroid nodules is increasing and the indeterminate interpretation rate of fine‐needle aspiration remains relatively high. The aim of the study is to review the published literature on automated image analysis and artificial intelligence applications to thyroid pathology with whole‐slide imaging. Methods Systematic search was carried out in electronic databases. Studies dealing with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…and mild nuclear atypia (chromatin margins, nuclear membrane irregularities, etc. ), which are confused with malignant lesions; cell enlargement can also be seen locally in benign thyroid tissue ( Girolami et al, 2020 ; Böhland et al, 2021 ). Benign thyroid tissue may also have a background of fibrosis and calcification at the background level, which is common in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…and mild nuclear atypia (chromatin margins, nuclear membrane irregularities, etc. ), which are confused with malignant lesions; cell enlargement can also be seen locally in benign thyroid tissue ( Girolami et al, 2020 ; Böhland et al, 2021 ). Benign thyroid tissue may also have a background of fibrosis and calcification at the background level, which is common in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A third observation is the application of AI for the automation of image analysis with whole-slide imaging ( 14 ). A recent study reported that the coefficients of correlation with manual evaluation were higher than 0.76 and that the diagnosis performance of the AI based robotized models was similar to a specialist pathologist analysis ( 14 ).…”
Section: The Application Of Ai To Thyroid Disorders: Preliminary Obse...mentioning
confidence: 99%
“…This will be particularly important in the context of clinical trials, evaluations of peer‐reviewed literature, or commercial studies. Examples include development or introduction of new molecular methods, validation of artificial intelligence routines for thyroid nodule assessment using ultrasound and histopathology, eg for assessment of ultrasound characteristics, 36 or morphometry of papillary carcinoma‐type nuclei to ascertain whether a particular lesion is benign or malignant 37 . It will therefore be essential that molecular pathology methods, histopathology terminologies, and cytopathology terminologies are very much aligned so that the clinical results obtained in one part of the world can be extrapolated with ease and utilised in other parts of the world.…”
Section: The Futurementioning
confidence: 99%
“…Examples include development or introduction of new molecular methods, validation of artificial intelligence routines for thyroid nodule assessment using ultrasound and histopathology, eg for assessment of ultrasound characteristics, 36 or morphometry of papillary carcinoma-type nuclei to ascertain whether a particular lesion is benign or malignant. 37 It will therefore be essential that molecular pathology methods, histopathology terminologies, and cytopathology terminologies are very much aligned so that the clinical results obtained in one part of the world can be extrapolated with ease and utilised in other parts of the world. In the authors' opinion the recently highlighted issue of the variation in cytopathology results obtained between Eastern and Western cytological practice 6 can be attributed to multidisciplinary treatment differences and diagnostic threshold differences, at least some of which are based on differing care pathways for the management of nodules.…”
Section: The Futurementioning
confidence: 99%